Implementing Actions On The Chest To Remove Sputum (Phlegm) In The Respiratory Tract That Is Not Normal - Nari, Jois; Surasno, Diah Merdekawati; Supriyatni, Nani; Rahayu, Agustin; Ali, St. Aminah; Nurnainah, Nurnainah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Sputum is a material expelled from the lungs and trachea through the mouth. Sputum expelled by a person should be able to be evaluated for its source, color, volume and consistency because the condition of sputum usually specifically shows the pathological process of the formation of sputum itself. The purpose of this study is to eliminate breathing difficulties caused by accumulation of secretions so that the client does not become tired when cleaning secretions and is able to expel phlegm optimally. The research method used is One Group Pre-test Post-test, which is a research design that only uses one group of subjects (without a control class) and carries out measurements before and after giving treatment to the subjects. The results of the study showed that the phlegm discharge in patients before the effective coughing exercise was carried out with the category of 54 people (60%) coming out and 36 people (40%) not coming out. The conclusion is that A significance value of <0.05 (p=0.000) was obtained, meaning that Ha was accepted, meaning that effective coughing exercises can increase phlegm excretion in patients.